2013
DOI: 10.2516/ogst/2013145
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement of the Gas Barrier Properties of Polyethylene and Polyamide Through the Nanocomposite Approach: Key Factors and Limitations

Abstract: Re´sume´-Renforcement des proprie´te´s barrie`re aux gaz de matrices polye´thyle`ne et polyamide par l'approche nanocomposite : facteurs cle´s et limitations -Dans cette e´tude, des nanocomposites sont pre´pare´s par voie fondue pour deux matrices, une matrice polyamide 6 (PA6) et une matrice polye´thyle`ne (PE), leur morphologie ainsi que leurs proprie´te´s barrie`res sont e´tudie´es. Les argiles organophiles sont choisies en fonction de la nature chimique de chacune des matrices polyme`res. Les nanocomposite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 45 publications
(53 reference statements)
1
23
0
Order By: Relevance
“…Different dispersion mechanisms could be proposed as a function of the nanocomposite compositions to explain the different obtained morphologies. In agreement with previous studies based on polyolefin/montmorillonite composites, it could be at first concluded that the use of a high molar mass compatibilizer was an efficient way to destroy the large aggregates in the system based on non‐modified LDH . The reinforcement of the filler/polymer interactions in a high viscosity medium allowed to take advantage of more efficient shearing process during the melting step and to finally obtain small tactoids.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Different dispersion mechanisms could be proposed as a function of the nanocomposite compositions to explain the different obtained morphologies. In agreement with previous studies based on polyolefin/montmorillonite composites, it could be at first concluded that the use of a high molar mass compatibilizer was an efficient way to destroy the large aggregates in the system based on non‐modified LDH . The reinforcement of the filler/polymer interactions in a high viscosity medium allowed to take advantage of more efficient shearing process during the melting step and to finally obtain small tactoids.…”
Section: Resultssupporting
confidence: 88%
“…Its melting temperature was 163 °C. Previous works performed on polyolefin based nanocomposites showed the interest of using high molar mass compatibilizer to achieve fine nanofiller dispersion with MMT type fillers …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The control of polymer hydration properties is a key parameter for a wide range of applications, going from biocompatible materials to barrier materials, packaging, breathable materials, or gas separation membranes. Different ways allowing the control of the hydrophilic/hydrophobic balance of the materials through blending route, copolymer route, (nano)composite approach, or development of hybrid organic/inorganic materials have been investigated to obtain a better control of both functional and mechanical properties for these applications. Among them, the copolymer route appears as particularly interesting as it allows to easily design different block lengths and natures and therefore to adjust functional properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, the difficulty to reach a complete exfoliation of the nanoplatelets often highly limits the gain in gas barrier properties . Moreover, the restricted choice of clay modifying agent makes difficult to promote strong interactions toward the PLA matrix when filler/matrix interfacial properties are identified by several authors as a key parameter to reach optimized barrier properties . In a green process approach, the combination of PLA with precipitated calcium carbonate nanofillers appears as an interesting route to be investigated.…”
Section: Introductionmentioning
confidence: 99%